Design and fabricate the new generation of working table - Teng, Boon Wun (2011)
Working table provide spaces for people to carry out variety of task. Based on market survey, there are various types of working tables. It is designed either to meet a specific task or designed to meet multipurpose task. Most of the working table can be used by more than 1 user, however, it is occupy space or vice versa. Few sketches on a new working table have been supported the requirements. Later, concept finalization is established which able to meet all the requirements. Solid work with dimension of actual product is designed. Zinc sheet metal and wood are chosen as the main materials in fabricate the prototype of the working table. Next, marking process, shearing and bending process, drilling process and joining process has undergone. The prototype design working table with the dimension scale of 1:2 is portable with the existence of castors and functional with the foldable table top and installment of whiteboard that act as the medium for dropping down information. Finally, finishing process is carried out to make the working table look more attractive. After that, analyses of stress and displacement have been carried out. The maximum load for the table top supporting mechanism and the storage compartments shelve are 330N and 550N respectively. From comparison study, actual design and prototype design are functional and equip with variety of criteria.